Characterizing haploinsufficiency of SHELL gene to improve fruit form prediction in introgressive hybrids of oil palm - Teh, Chee Keng; Muaz, Siti Dalila; Tangaya, Praveena; Fong, Po-Yee; Ong, Ai Ling; Mayes, Sean; Chew, Fook Tim; Kulaveerasingam, Harikrishna; Appleton, David Ross (Nature Publishing Group, 2017)
The fundamental trait in selective breeding of oil palm (Eleais guineensis Jacq.) is the shell thickness surrounding the kernel. The monogenic shell thickness is inversely correlated to mesocarp thickness, where the crude palm oil accumulates. Commercial thin-shelled tenera derived from thick-shelled dura × shell-less pisifera generally contain 30% higher oil per bunch. Two mutations, shᴹᴾᴼᴮ (M1) and shAVROS (M2) in the SHELL gene – a type II MADS-box transcription factor mainly present in AVROS and Nigerian origins, were reported to be responsible for different fruit forms. In this study, we have tested 1,339 samples maintained in Sime Darby Plantation using both mutations. Five genotype-phenotype discrepancies and eight controls were then re-tested with all five reported mutations (shAVROS, shᴹᴾᴼᴮ, shᴹᴾᴼᴮ², shᴹᴾᴼᴮ ³ and shᴹᴾᴼᴮ⁴) within the same gene. The integration of genotypic data, pedigree records and shell formation model further explained the haploinsufficiency effect on the SHELL gene with different number of functional copies. Some rare mutations were also identified, suggesting a need to further confirm the existence of cis-compound mutations in the gene. With this, the prediction accuracy of fruit forms can be further improved, especially in introgressive hybrids of oil palm. Understanding causative variant segregation is extremely important, even for monogenic traits such as shell thickness in oil palm.